Changes in ocean circulation and carbonate chemistry in the Australian sector of the Southern Ocean during the last 500,000 years - Sturm, Arne (2003)
Stable oxygen and carbon isotope records and carbonate dissolution proxy records were used to reconstruct glacial/interglacial changes in ocean circulation, deep-water ventilation and carbonate chemistry in the Australian sector of the Southern Ocean for the last 500 kyr. Carbonate preservation records indicated a longitudinal gradient in Southern Ocean deep-water alkalinity at 110°E that persisted through glacial/interglacial stages. In contrast to previous studies suggesting the “Atlantic-type” carbonate preservation pattern in the entire Southern Ocean with enhanced carbonate preservation during interglacials and increased carbonate dissolution during glacials, this study, however, revealed that the reversed “Pacific-type” pattern of glacial/interglacial carbonate preservation expanded from the Pacific into the Australian sector of the Southern Ocean up to 110°E. This result implies that deep-waters in the Australian sector flow westwards against the predominant eastward drift in the Southern Ocean. Epibenthic stable carbon isotope records depicted a detailed variability of Pleistocene deep-water circulation and ventilation with new implications for glacial deep-water circulation. The major problem in understanding the glacial deep-water circulation and isotope signatures below 2,500 m derives from the extremely low delta13C values in the Atlantic-Indian sector of the Southern Ocean contrasting relatively high delta13C values in the central Pacific. The glacial delta13C signatures of deep-waters in the Australian sector represent a mixture of both endmembers and thus link the isotope signatures of both regions. This suggests a westward deep-water flow to the south of Australia, which is consistent with the “Pacific-type” pattern of carbonate preservation in this area. These findings suggest the SW Pacific, in particular the Ross Sea, as a source region for nutrient-depleted Glacial Antarctic Bottom Water, which ventilated both, the Australian sector of the Southern Ocean and the deep Pacific. Considering the ...